Men's preconception health and the social determinants of health: What are we missing? - Anakwe, Adaobi; Xian, Hong; BeLue, Rhonda; Xaverius, Pamela (Frontiers in Reproductive Health, 2022)
Background Life course perspectives suggest that optimizing men's health before conception is requisite to equitably improve population health, an area of increasing public health focus. Although scholarship on the social determinants of health (SDOH) suggests that men's health and health behaviors do not occur in a vacuum, preconception health studies have not explicitly examined how these factors influence men's preconception health. Objective To identify latent classes of men's preconception health and the role of the SDOHs in predicting class membership. Methods Pooled data from the 2011–2019 male file of the National Survey of Family Growth were analyzed (n = 10,223). Latent class analysis (LCA) was used to identify distinct classes of men's preconception health. Eight manifest variables were used to fit latent class models. A classify-analyze approach was subsequently used to create a preconception health phenotype (PhP) outcome variable. SDOHs (exposure variable) were assessed in four domains (rural/urban residence, health access, socioeconomic status, and minority/immigrant status) to predict class membership. Survey-weighted multinomial regression models were fitted to examine the association between the exposure and the outcome. Results Three unique PhPs were identified (lowest risk (69%), substance users (22.9%), and sexual risk-takers (8.1%) from the LCA model. Health access, socioeconomic status, and minority/immigrant status were significant predictors of class membership but not rural/urban residence. Sexual risk takers were more likely to be uninsured (aOR: 1.25, 95% CI 1.02, 1.52), college-educated (aOR: 1.94 95% CI: 1.34, 2.79), and non-Hispanic Black (aOR: 1.99 95% CI: 1.55, 2.54) while substance users were more likely to have unstable employment (aOR: 1.23 95% CI:1.04, 1.45) and have a high school degree or higher (aOR 1.48 95% CI: 1.15, 1.90) than men in the lowest risk category. Conclusion Social determinants may impact men's preconception health in ways that are not conventionally understood. These findings raise important questions about how preconception health interventions should be created, tailored, and/or retooled. Specifically, studies that examine the sociocultural and political contexts underpinning the relationship between social class, masculinity, and men's preconception health are needed to provide nuanced insights on factors that shape these outcomes.